Willingness to pay for hepatitis B virus vaccine and associated factors among households in Bahir Dar City, northwest Ethiopia: using contingent valuation method - Aychew, Addis; Minyihun, Amare; Tsehay, Chalie Tadie; Amare, Tsegaw; Aschalew, Andualem Yalew (Frontiers in Public Health, 2023)
Background The prevention of disease burden and death through vaccination is one of the most cost-effective methods. Even though the Hepatitis B Virus (HBV) has significant public health problems in Ethiopia, there is no compulsory HBV vaccination program for adults and the vaccine's market value was not yet estimated in the Ethiopia context. Therefore, this study aimed to assess the willingness to pay (WTP) for the HBV vaccine and its associated factors among households in Bahir Dar City, northwest Ethiopia. Methods A cross-sectional study was conducted among 620 households from March 1 to 30, 2020. A systematic random sampling technique was employed to select the required number of households. An interviewer-administered questionnaire was used to collect the necessary information. The contingent valuation method was conducted to measure WTP for the HBV vaccine. A Tobit regression model was employed to investigate significantly associated factors, and variables with a p-value of <0.05 were considered statistically significant. Results In this study, 62.17% of households were willing to pay for the HBV vaccine with an average cost of ETB174.24 (US$5.25). Male household heads (P = 0.014), favorable attitude (P = 0.017), and good knowledge (P < 0.001) toward the vaccine were positively associated with WTP, whereas age (P < 0.001), single marital status (P = 0.012) and divorced/widowed (P = 0.018) marital status were negatively associated with WTP. Conclusions Overall, most households were willing to pay for the HBV vaccine with an average demand of ETB174.24 (US$5.25). Therefore, a national-level HBV vaccine strategy should be designed considering the households' willingness to pay. In addition, working on attitudes and knowledge toward the vaccine could potentially increase the household's willingness to pay for the HBV vaccine.